Transparent low-flammability epoxy resins using a benzoguanamine-based DOPO derivative. (March 2022) - Han, Xiao; Chen, Rui; Yang, Mei; Sun, Chuanbo; Wang, Kun; Wang, Yinsong
We successfully prepared a highly effective flame-retardant additive called hsalbenzoguanamine phosphaphenanthrene (HDPD) through salicylaldehyde and nitrogen-rich benzoguanamine. The introduction of HDPD into epoxy resin (EP) sharply enhanced the flame retardancy of EP/HDPD thermosets. The introduction of 6 wt% HDPD into EP succeeded in reaching the V-0 rating. Limited oxygen index results revealed the high flame-retarding performance of HDPD. Cone calorimeter test data revealed that heat and smoke released from EP/6 wt% HDPD thermoset were significantly restrained. In addition, EP/6 wt% HDPD thermoset demonstrated excellent transmittance and mechanical strength. The transmittance of EP/6 wt% HDPD was assessed from 520 to 800 nm. The results showed that transmittance of EP/6 wt% HDPD were nearly 90% of the control group.